ANALISIS PROSES PEMBELAJARAN E-LEARNING BERBASIS EDMODO DALAM MENINGKATKAN HASIL BELAJAR SISWA - Alyan Fatwa; Samsudin Samsudin (Akademika : Jurnal Teknologi Pendidikan, 2022)
The use of Edmodo in the online learning process can be used in activities carried out within school and outside of school, in the use of Edmodo in class X at SMAN 1 Slawi and MAN 1 Tegal Regency can be maximized with the facilities provided by the school. In its use outside of school, edmodo can be used by students by utilizing computers, laptops or notebooks and android phones that are in students' homes, this research was conducted to analyze the implementation of e-learning learning using edmodo in improving the learning outcomes of class X students in SMAN 1 Slawi and MAN 1 Tegal Regency. The research objectives in this study are as follows: To provide an explanation of the implementation of Edmodo-based e-learning learning in improving the learning outcomes of class X students at SMAN 1 Slawi and MAN 1 Tegal Regency. Provide an explanation of the implications of implementing Edmodo-based e-learning in improving the learning outcomes of class X students at SMAN 1 Slawi and MAN 1 Tegal Regency. This research is a classroom action research conducted through a collaborative work process of mathematics teachers, researchers, and school principals as well as other concerned educators and education personnel. In its original term, Classroom Action Research is called Classroom Action Research. Based on the findings and results of research on the use of the Edmodo application, it turns out that it can improve students' mathematics learning outcomes about the concept of absolute value in class X students at SMA Negeri 1 Slawi and MAN 1 Tegal. So overall student learning outcomes have increased when viewed from the average value obtained by students in class X.